The Role of Extrinsic and Intrinsic Motivation on Adults' Tendency towards Physical Activity - Ahmad Rahmani; Javad Salehi; Maryam Azarshin; Tayebeh Bakhshi Nia (University of Tehran, 2011)
Researchers demonstrate that individuals in different levels of physical activity have different motivations for sport activity. This study was designed to examine how motivations can discriminate three physical activity levels (inactive, active, sustained maintainers) according to self-determination theory. 159 Zanjan University staff (mean age: 33 years old) completed exercise motivation inventory (EMI-2) and stage of change scale. Using confirmatory factor analysis, construct validity of EMI-2 was established. Six factors were confirmed in the EMI-2: Health and fitness, social - emotional benefits, weight management, stress management, enjoyment and appearance. Results showed that enjoyment, stress management and social - emotional benefits differentiated physical activity levels. Interaction of age and sex was not significant. It was concluded that intrinsic motivation (enjoyment) and extrinsic self-determined motivation (stress management, social - emotional benefits) played an effective role in changing behavior and increasing physical activity.